KARAKTERISTIK DAN KANDUNGAN GIZI TSUKUDA-NI IKAN JANGILUS (Istiophorus orientalis) - Sri Purwaningsih; Agoes M Jacoeb; Masikah Maylan Dewi (Asian Journal of Innovation and Entrepreneurship, 2012)
Jangilus fish ( Istiophorus orientalis) is one of pelagic commodities which is commonly consumed by society and used for traditional foods. The objective of this research was to determine the effect of immersion solution on tsukuda-ni from Jangilus fish (Istiophorus orientalis). The steps of the research were determine the best type of immersion solution (carbonated drink, rice vinegar, soy sauce, or sweet sake) and the best concentrations of solution (10%, 20%, 30%, 40%, 50% dan 60% [v/v]). The experimental design used in this experiment was complete random design with Tukey test. The study showed that carbonated drink was the best type of immersion solution. The statistical analysis results showed that concentrations of solutions immersion gave significant effect on protein, lipid content, cutting strength, and water activity. The study showed that 40% carbonated drink was the best concentrations. Tsukuda-ni with 40% of the carbonated drink had 30.95 ± 1.20 kg/cm2 power cut, 0.73 water activity (aw), 61.02% water, 4,48% ash, 28,89 % protein, 0,34% fat, and 4,49% carbohidrat content. Keywords: Fish jangilus (Istiophorus orientalis), tsukuda-ni, nutrient content